Mirages of development : science and technology for the third worlds - Salomon, Jean-Jacques; Lebeau, Andre (Boulder : Lynne Rienner Publishers, 1993)
Economics
Includes index and bibliographical references
2000-08-09
Keywords: Technological innovations; Technology transfer; Developing countries